2004
DOI: 10.1038/sj.bdj.4811389
|View full text |Cite
|
Sign up to set email alerts
|

The current working patterns and future career aspirations of specialist trainees in dentistry

Abstract: ObjectivesTo determine current demographic details of dental specialist registrars in the UK, to examine their current working patterns and ascertain their future career aspirations. Methods A cross-sectional survey, using a self-administered postal questionnaire of all 418 dental specialist registrars (SpRs) in the UK. Results The response rate was 78%. Of the SpRs who responded 59% were male, the majority were aged under 36, 54% were married and over one third had dependants. Orthodontics had the greatest nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
0
14
1
Order By: Relevance
“…4 Previous studies have also found an increase in the number of female dentists specialising and significant gender differences within specialities. 8,15 Following DFT, the majority (93%) of respondents intend on working full-time, although this drops to 77% after 5 years and to 48% after 15 years. Furthermore, after 5 years and 15 years, the percentage of females who intend on working part time (62%) is more than double the percentage of males (29%).…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have also found an increase in the number of female dentists specialising and significant gender differences within specialities. 8,15 Following DFT, the majority (93%) of respondents intend on working full-time, although this drops to 77% after 5 years and to 48% after 15 years. Furthermore, after 5 years and 15 years, the percentage of females who intend on working part time (62%) is more than double the percentage of males (29%).…”
Section: Discussionmentioning
confidence: 99%
“…Why this occurred is not immediately obvi ous from the questionnaire, as this aspect was not investigated. There is some evi dence that flexible training is particularly appreciated by women 6 and the replies to the question on a career in medicine may have been influenced by this factor.…”
Section: Discussionmentioning
confidence: 99%
“…4,[12][13][14][15] Despite this, little is known as to whether the cultures and traditions of minority ethnic groups affect the sup ply of orthodontic personnel. 12,16 The aims of this study were to examine the demographics of the current special ist orthodontic workforce and explore any trends which may exist in the gen der and ethnic balance of those on the Specialist List in Orthodontics.…”
Section: Introductionmentioning
confidence: 99%